Determinants of household nutrient intake and preschoolers' nutritional status in two rural villages in the Philippines - Mia, Mohammed Moslem Uddin 1954-; Florencio, Cecilia A. (1996., 1996)
The study aimed to determine the effects of agricultural and socioeconomic factors on the nutrient intake of farms households and the preschoolers' nutritional status. This study was conducted in two rural villages in the Philippines. All of the farm households which had at least a preschool child below 6 years old were included in the study. There were 41 households with a total of 64 preschool children. Information on crop production, income, expenditure, and food intake of farm households at the household level and anthropometric measurements --e.g., age, sex, weight and height of the preschoolers-- were collected in May 1996, Food frequency questionnaire (FFQ) method was used to obtain food intake data. A comparison was also made between nutrient intake at the household level and that of the same households based on information collected in 1989-91. The nutritional status of the preschool children in farm households was also compared with that in 1991. Nutrient intakes at the household level were significantly higher in 1996 than those in the 1989-91. There were no significant differences in nutritional status of preschool children between the two periods, 1996 and 1989-91. Using the stepwise regression analysis, household size and per capita food expenditure were found to be significant determinants of per capita energy intake. Agricultural factors such as per capita landholding, tenurial status and crop production did not show significant influence on per capita energy intake, but the agricultural variables together explained 41% variance in the model. Another regression analysis, using the same technique, was done to identify the significant determinants of preschoolers' nutritional status. Per capita landholding, tenurial status, crop production and household size of the farm households, and age and sex of the preschoolers were found to be significant determinants of nutritional status for both as percent of local standard and Z-scores of international standard. From the findings, it can be concluded that the effect of agricultural factors of farm households are evident at the individual level but not at the household level. They are significant determinants, in addition to socioeconomic and child's biological factors, of preschoolers' nutritional status but no of energy intake at the household level. The socioeconomic factors such as household size and food expenditure are the significant determinants of energy intake at the household level.
Computer print-out.
Thesis (Ph. D. Nutrition)--University of the Philippines, Diliman.
Vita.
Keywords: Ingestion; Nutrition -- Evaluation, Philippines; Preschool children -- Nutrition